Pemanfaatan Pelayanan Kesehatan pada Anak Indonesia: Pengaruh Kemiskinan dan Karakteristik Ibu - Ririn Kuncaraning Sari; Dwini Handayani (Faculty of Public Health, Hasanuddin University, Makassar, 2020)
The utilization of health care is an important determinant to improve health status, especially for children. However, poverty and parental characteristics especially mothers are important determinants of healthcare utilization for children. This uses the Indonesia National Socio-Economic Survey (SUSENAS) 2017 and Village Potential Statistic (PODES) 2018 to study the effect of that variable on outpatient healthcare utilization for children. The sample in this research is 50.437 children who have health complaints, disrupted activity in the past month, and living with mother. Data analysis was carried out descriptively and using logistic regression. The result showed that one out of three children does not utilizing healthcare for outpatient when sick. Furthermore, logistic regression shows that family poverty has a negative and significant effect on the children’s utilization of healthcare for outpatient in Indonesia (OR=0,79). While maternal education and employment status have a significant and positive effect. This result showed that there are necessary to provide ease access to healthcare for the children in a poor household and to improve maternal empowerment to be able to increase the utilization of healthcare especially outpatient care for children.